Numerical study on hysteretic characteristics of transmission tower K-joints - Zhang, Jian; Wu, Guangchen; Yang, Lidong (Frontiers in Materials, 2022)
The mechanical properties of joints have a significant impact on the dynamic response of transmission tower structures. Considering bolt slip, the numerical model of transmission tower K-joint is established. The mechanical properties of K-joints are studied from three aspects: failure mode, load-displacement hysteretic curve and stiffness degradation by numerical method. The effects of bolt preload, friction coefficient and member strength on the hysteretic properties of K-joint are analyzed. The results show that due to the complexity of K-joints, bolt slip will lead to the reduction of ultimate bearing capacity and the change of failure position. In order to accurately obtain the mechanical properties of K-joints, the influence of bolt slip should be considered in the research process; The plumpness of load-displacement hysteretic curve is greatly affected by parameters; The stiffness of K-joints degenerates with the increase of loading times. The results provide a reference for the mechanical analysis of transmission tower.